2016
DOI: 10.1111/cei.12800
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of miR-146a/FAS and miR-21/FASLG axes in autoimmune lymphoproliferative syndrome due to FAS mutation (ALPS-FAS)

Abstract: 1These authors contributed equally to the study. SummaryMost cases of autoimmune lymphoproliferative syndrome (ALPS) have an inherited genetic defect involving apoptosis-related genes of the FAS pathway. MicroRNAs (miRNAs) are a class of small non-coding regulatory RNAs playing a role in the control of gene expression. This is the first report on miRNAs in ALPS patients. We studied a mother and son carrying the same FAS cell surface death receptor (FAS) mutation, but with only the son manifesting the signs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…CD4 1 T cells are an important subpopulation of T cells which play a central role in innate immune responses, maintaining the balance of anti-inflammatory and proinflammatory responses, promoting activation of antigenpresenting cells (APCs) and B cells as well as promoting the accumulation of immune cells [33][34][35][36][37]. Increasing evidence demonstrates that the distinct miRNA molecule plays a critical regulatory role in the development and function of various immune cells, including CD4 1 T cells, which affect the pathogenesis and development of related clinical diseases [38][39][40][41][42][43][44]. For example, Zeng et al [45] reported that down-regulation of miR-451a affects the activation and proliferation of CD4 1 T cells by targeting the transcription factor myelocytomatosis oncogene (Myc) in dilated cardiomyopathy (DCM) patients, which contribute to the immunopathogenesis of DCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 1 T cells are an important subpopulation of T cells which play a central role in innate immune responses, maintaining the balance of anti-inflammatory and proinflammatory responses, promoting activation of antigenpresenting cells (APCs) and B cells as well as promoting the accumulation of immune cells [33][34][35][36][37]. Increasing evidence demonstrates that the distinct miRNA molecule plays a critical regulatory role in the development and function of various immune cells, including CD4 1 T cells, which affect the pathogenesis and development of related clinical diseases [38][39][40][41][42][43][44]. For example, Zeng et al [45] reported that down-regulation of miR-451a affects the activation and proliferation of CD4 1 T cells by targeting the transcription factor myelocytomatosis oncogene (Myc) in dilated cardiomyopathy (DCM) patients, which contribute to the immunopathogenesis of DCM.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cells are an important subpopulation of T cells which play a central role in innate immune responses, maintaining the balance of anti‐inflammatory and proinflammatory responses, promoting activation of antigen‐presenting cells (APCs) and B cells as well as promoting the accumulation of immune cells . Increasing evidence demonstrates that the distinct miRNA molecule plays a critical regulatory role in the development and function of various immune cells, including CD4 + T cells, which affect the pathogenesis and development of related clinical diseases . For example, Zeng et al .…”
Section: Discussionmentioning
confidence: 99%
“…30 It seems that hypoexpression of a miRNA, mir-146a, can promote Fas expression. 31 Previous studies draw our attention to a mir-146a polymorphism, namely, rs2910164, a G/C change that results in an alteration of the amino acid sequence that leads to a mismatch in the stem-loop of miRNA, which was determined to modify mature mir-146a's expression level and therefore is associated with the susceptibility to various autoimmune disorders such as RA 32 and BD. 33 Our findings are in line with previous reports in the literature that found the wild type of rs2910164 has a protective function in BD.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-146a gene is located in 5q34 and plays roles in diverse fields, including tumorigenesis, respiratory diseases pathogenesis, and immune reaction. MiRNA-146a was previously reported to be involved in cancer development and autoimmune disease (Bogunia-Kubik et al 2016 ; Kotlarek et al 2018 ; Marega et al 2016 ). Recently, Hsa-miR-146a-3p was found be to a regulator of macrophage differentiation and M1/M2 polarized activation processes (Essandoh et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%